2022
DOI: 10.2174/18742858-v16-e2201310
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Dissemination of BLBLI-Resistant Enterobacter cloacae from Public Hospitals in Baghdad, Iraq

Abstract: Background: Enterobacter cloacae are most frequently isolated from human clinical specimens. Objective: This cross-sectional study aimed to investigate the dissemination of E. cloacae clinical isolates resistant to β-lactam-β-lactamase inhibitor (BLBLI) combinations from different clinical specimens of hospitalized patients. Methods: E. cloacae isolates were recovered from different clinical samples of hospitalized patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this present study, about 30.15 percent of the cultured samples tested positive for considerable bacterial growth. Similar findings were seen in earlier studies carried out in several Iraqi districts (Sabry et al, 2021), while some other studies reported higher growth rates (Alzaidi and Mohammed, 2022;Al-Asady et al, 2022). This ratio of no growth results from those patients who probably uptake antibiotics, suffering from a viral infection, immunological disorder, or other conditions.…”
Section: Discussionsupporting
confidence: 90%
“…In this present study, about 30.15 percent of the cultured samples tested positive for considerable bacterial growth. Similar findings were seen in earlier studies carried out in several Iraqi districts (Sabry et al, 2021), while some other studies reported higher growth rates (Alzaidi and Mohammed, 2022;Al-Asady et al, 2022). This ratio of no growth results from those patients who probably uptake antibiotics, suffering from a viral infection, immunological disorder, or other conditions.…”
Section: Discussionsupporting
confidence: 90%
“…In the last decades bacterial infections have become one of the most biggest threats to human health and food security globally [47,48]. Several studies indicated a rapid and uncontrolled spread of antibiotic resistant bacteria among Iraqi patients [49][50][51]. Local studies identified the contamination of Iraqi rivers water with antibiotic-resistant bacteria [52].…”
Section: One-step Growth Curvementioning
confidence: 99%